2023
DOI: 10.56225/ijfeb.v2i1.47
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Political Risk and Macroeconomics Factors Towards Foreign Direct Investment in Developing Countries

Abstract: This study examines the relationship between macroeconomic factors and foreign direct investment (FDI) inflows in developing countries. The data from the World Bank covers 21 years, from 2000 to 2020 was analyzed using the panel regression approach with E-Views. Panel regression analysis, including model selections and diagnostics, is used for inferential analysis. The main contribution of this study is the influence of political factors on FDI inflows. Political stability and corruption control are technicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Several studies have examined the relationship between exchange rates and FDI, focusing on factors such as exchange rate volatility, trade openness, GDP, and other macroeconomic variables. The study done by Mohamad et al (2023) discovered that the exchange rate, exports, and political stability have a negative relationship with the level of FDI in developing countries. Kiyota and Urata (2004) found that exchange rate volatility has a positive impact on FDI.…”
Section: Exchange Rate (Exe)mentioning
confidence: 99%
“…Several studies have examined the relationship between exchange rates and FDI, focusing on factors such as exchange rate volatility, trade openness, GDP, and other macroeconomic variables. The study done by Mohamad et al (2023) discovered that the exchange rate, exports, and political stability have a negative relationship with the level of FDI in developing countries. Kiyota and Urata (2004) found that exchange rate volatility has a positive impact on FDI.…”
Section: Exchange Rate (Exe)mentioning
confidence: 99%